Potential for Communicating Through Cable TV in Texas - Larry A. Quinn (Journal of Applied Communications, 1973)
As we began to think of the potential for using Texas cable television (CATV) systems in communicating extension educational and news information on a statewide basis, we felt we first needed some reactions from the cable systems.